Relationship On Business Behavior In The Implementation Of Sanitation Hygiene And Food Management In The Home Industry In Johan Districts Pahlawan West Aceh District - Aris Winandar; Riski Muhammad; Zakiyuddin Zakiyuddin (Journal of Nutrition Science, 2020)
Indonesia has experienced 115 extraordinary events (KLB) due to food poisoning. In addition, it is also known that food poisoning in Indonesia is caused by household processed food products amounting to 40.87% and processed food products amounting to 24.35%. The food home industry in West Aceh is as many as 48 businesses while in Johan Pahlawan District there are as many as 40 businesses. This study aims to determine the relationship between entrepreneurial behavior in the application of sanitation hygiene and food management in the home industry in Johanahlawan subdistrict, Aceh Barat district. This research is a descriptive analytic study with a cross sectional design, with a population of 40 with the sample in this study are 40 home industry entrepreneurs in johan Pahlawan district. The sampling technique in this study using the total sampling method. Based on the research results, it shows that the independent variables (attitude and action) have a relationship with food management where Pvalue <α (0.05) while Knowledge has no relationship where Pvalue> α (0.05).To related agencies, to further improve counseling, supervision and monitoring of household Home Industry and to household Home Industry entrepreneurs to further increase their awareness of the importance of managing food well.